1993
DOI: 10.1381/096089293765559106
|View full text |Cite
|
Sign up to set email alerts
|

Resting Energy Expenditure in Long-Term Postobese Subjects after Weight Normalization by Dieting or Biliopancreatic Diversion

Abstract: Resting energy expenditure (REE) was measured by Indirect calorimetry in three groups of subjects closely matched for body weight (BW) and body composition. Five subjects had reduced from lO3 kg (129-90) to normal BW by dieting. Fourteen subjects had normalized their weight (preop 120 kg, from 168 to 100) following biliopancreatic diversion (BPD). All subjects in both groups had essentially maintained a stable weight for at least 2 years before the study. Ten healthy volunteers who had never been obese served … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 0 publications
0
3
1
Order By: Relevance
“…In fact, the massive weight loss of RYGB occurs in the setting of metabolic adaptation (decreased energy demands greater than expected for the degree of weight loss), suggesting the contribution of hormonal or neuronal factors (or both) in the anorectic effect 110 . The effects of RYGB on energy expenditure appear to be contrary to those observed in BPD, which Scopinaro and colleagues have reported 111 . Overall, when examining the metabolic and body weight changes observed both acutely and chronically by RYGB and comparing those with BPD, researchers are tempted to speculate that the BPD operation represents an extreme physiologic response.…”
Section: More Than Gastric Restriction: Operations With Hormonal Effecontrasting
confidence: 62%
“…In fact, the massive weight loss of RYGB occurs in the setting of metabolic adaptation (decreased energy demands greater than expected for the degree of weight loss), suggesting the contribution of hormonal or neuronal factors (or both) in the anorectic effect 110 . The effects of RYGB on energy expenditure appear to be contrary to those observed in BPD, which Scopinaro and colleagues have reported 111 . Overall, when examining the metabolic and body weight changes observed both acutely and chronically by RYGB and comparing those with BPD, researchers are tempted to speculate that the BPD operation represents an extreme physiologic response.…”
Section: More Than Gastric Restriction: Operations With Hormonal Effecontrasting
confidence: 62%
“…After weight loss, significant reductions in energy expenditure favoring the regain of lost weight have been shown [38][39][40]. However, after biliopancreatic diversion (BPD), energy expenditure studied at different time-points has been observed to be significantly higher than that of nonobese controls [41]. Moreover, in rat models, it has been shown that the BPD induces a negative energy balance [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, all of the many obese women with a preoperative TEE lower than 1750 kcal/day lost weight after BPD. Therefore an increase of energy expenditure after BPD had to be hypothesized, already suggested by three previous studies [13][14][15] demonstrating that after BPD there was an energy expenditure greater than what was theoretically expected after the observed weight reduction.…”
Section: Weight Maintenancementioning
confidence: 93%